Health information : management of a strategic resource 2026-02-15T15:52:19+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Abdelhalim (Saunders/Elsevier, 2007)

(untitled)
Gives prospective health information management professionals the knowledge, confidence, and practical application experience to succeed in health informatics